Prediction of biophysical attributes for high yielding genotypes of bitter gourd (Momordica charantia L.) for rainfed condition (Indian Journal of Arid Horticulture, 2013)
An investigation on prediction model to identify suitable genotype by character association and path analysis was  undertaken with forty-six genotypes of bitter gourd. The results revealed that in general, the genotypic correlation  coefficients were higher than the corresponding phenotypic correlation coefficient level. The fruit yield per plot had a  strong positive and significant association with number of female flowers per plot, number of fruits per plot, fruit girth, fruit  length, number of primary branches and main vine length. Node of first female flower appeared and days to first fruit  harvest showed negative association with yield. The path analysis revealed that fruit length, 100 seed weight, no. of female  flower per plot, no. of fruits per plot, no. of primary branches per plant and main vine length exhibited strong positive direct  effect on yield per plot. Days to first fruit harvest, no. of seeds per fruit, fruit girth had direct negative effect on yield. Hence  the selection based on these characters will be effective in formulating selection indices for improvement of high yielding  genotypes in bitter gourd for zero irrigation system.
Keywords: Biophysical attributes; high yield; bitter gourd; rainfed condition